Letter (copy) - Tewson, Vincent
026-0130-001 Secretary's. HVT/FC/422. 4th April, 1939. Mr. Pascual Tomas-Taengua, c/o M. Rene Desbals, Secretary of the Socialist Party, S.F.I.O., Rue Raur, TOULOUSE. Dear Mr. Tomas, Sir Walter Citrine has been away serving on a Government Committee in the West Indies for some time and is due to return within the next week. I know he will be deeply concerned, as we are, in regard to the contents of your letter which was received this morning. I am immediately communicating with Mr Schevenels, Secretary of tne International Federation of Trade Unions, forwarding a copy of your letter and inquiring as to the possibility of early contact being made with you. We feel very deeply the position of our Spanish colleagues at the present time, and I know that through the International Federation of Trade Unions such action is being taken as is possible with the limited funds at their disposal. In spite of the present gloomy situation I hope that Mr. Schevenel's contact with you will afford some relief and that some of the immediate difficulties will be overcome. I quite realise how you feel not having had any news of your wife and family who are in Spain, and I do hope that you may soon be informed of their safety. Reciprocating your cordial greetings, I am, Yours sincerely, Assistant Secretary. 292/946/26/130